1996
DOI: 10.1177/074823379601200501
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Feeding Exposure of Infants To Environmental Contaminants — a Public Health Risk Assessment Viewpoint: Chlorinated Dibenzodioxins and Chlorinated Dibenzofurans

Abstract: Exposure of children to chlorinated dibenzodioxins and chlorinated dibenzofurans via breast-feeding has been well-documented in industrialized countries. Recent studies indicate a possible link between development of subtle health effects in children and their exposure to dioxin-like chemicals from maternal milk. Some examples of the effects are lower vitamin K levels, increased thyroxine levels, and mild changes in liver enzymes. The projected daily intakes of chlorinated dibenzodioxins and chlorinated dibenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…There is mounting experimental evidence suggesting that TCDD may affect human fertility, because it is associated with anovulation and dysfunctional spermatogenesis in primates and other animals (32)(33)(34)(35). Developmental anomalies in infants may arise as a result of exposure via breast milk (36). Epidemiological studies have indicated that TCDD exposure is associated with an increase in many types of cancer, including lung, liver, and rectal cancers (3).…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting experimental evidence suggesting that TCDD may affect human fertility, because it is associated with anovulation and dysfunctional spermatogenesis in primates and other animals (32)(33)(34)(35). Developmental anomalies in infants may arise as a result of exposure via breast milk (36). Epidemiological studies have indicated that TCDD exposure is associated with an increase in many types of cancer, including lung, liver, and rectal cancers (3).…”
Section: Discussionmentioning
confidence: 99%
“…These gaps can be filled through human epidemiologic study. Consideration of the high milligrams per kilogram per day dose delivered to the nursing infant and the persistence of the delivered dose for nearly a lifetime may require modifications in regulatory risk assessment models for persistent, biocumulative chemicals and for chemicals that can cross the placenta ( Pohl and Hibbs, 1996;Abadin et al, 1997) .…”
Section: Discussionmentioning
confidence: 99%
“…Also the differences between them are instructive. Risk-benefit comparisons in connection with contaminants in human milk and breastfeeding have been noted as an important topic on several occasions (e.g., Clench-Aas et al 1992, Pohl and Hibbs 1996. In general, it has been stressed that contaminants do not justify discouragement and reduction of breast-feeding.…”
Section: Breast-feeding As a Parallel Case Of Risk-benefit Balancingmentioning
confidence: 99%